A Coaching Session Framework to Facilitate Long-Term Athletic Development. Issue 3 (June 2021) - Till, Kevin; Eisenmann, Joe; Emmonds, Stacey; Jones, Ben; Mitchell, Tom; Cowburn, Ian; Tee, Jason; Holmes, Neil; Lloyd, Rhodri S.
Abstract : ABSTRACT: The implementation of long-term athletic development (LTAD) aims to improve health, physical activity, and performance of all youth. Contemporary LTAD models suggest that a broad range of physical and psychosocial competencies should be developed in youth, but few resources are available for coaches that describe "how" to achieve these outcomes. This article overviews a coaching session framework built around the following components: raise, activate, mobilize, prepare, activity, games, evaluate (RAMPAGE). The framework provides practitioners with information on what can be planned and delivered and when within a coaching session, across multiple ages and stages of development within multiple contexts (e.g., physical education and talent development).